STRATEGIES FOR ALIGNING VOCATIONAL SCHOOLS WITH THE BUSINESS AND INDUSTRIAL WORLD IN THE ERA OF THE INDUSTRIAL REVOLUTION 5.0 - Caca Andika; Rg Guntur Alam (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Aligning vocational schools with the business and industrial world is a crucial need in facing the dynamics of the Industrial Revolution 5.0, which is characterized by advances in smart technology and demands for an adaptive and innovative workforce. This study aims to analyze strategies for aligning vocational education with the needs of technology-based industries through a systematic literature review of 45 national and international articles published in 2015–2025. Articles were selected based on inclusion criteria relevant to the themes of vocational curriculum, industrial work practices, skills development, and school–industry partnerships. Contributions to novelty(novelty)This research emphasizes the integration of soft skills, digital literacy, and smart technology-based industrial partnerships in vocational alignment strategies. This focus complements previous research that generally still emphasizes aspects of the curriculum or conventional field work practices. The results of the study indicate that effective alignment includes four main aspects: developing a competency-based curriculum that is responsive to industry dynamics, implementing relevant internships and work practices, strengthening soft skills such as communication, leadership, and critical thinking, and building sustainable partnerships with the digital technology-based business world. Strong synergy between vocational schools and industry has proven to be a key factor in preparing graduates who are work-ready, globally competitive, and able to innovate in the era of advanced technology. This research recommendation emphasizes the need for an adaptive and sustainable alignment strategy, especially through the integration of digital literacy, 21st-century skills, and industry 5.0 collaboration networks, so that vocational education becomes increasingly relevant in supporting the development of superior human resources for the advancement of the national economy and industry.